2021
DOI: 10.1093/jxb/erab058
|View full text |Cite
|
Sign up to set email alerts
|

Resolving a QTL complex for height, heading, and grain yield on chromosome 3A in bread wheat

Abstract: Crop height (Ht), heading date (Hd), and grain yield (GY) are interrelated in wheat. Independent manipulation of each is important for adaptation and performance. Validated QTL for all three collocate on chromosome 3A in the Avalon x Cadenza population with increased Ht, Hd, and GY contributed by Cadenza. We asked if these are linked or pleiotropic effects using recombinant lines and showing that Ht and Hd effects are independent. The Chinese Spring equivalent to the newly defined Ht interval contained a gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The latter is flanked by two previously reported SSR markers Xbarc45 (Griffiths et al 2009) and WMC264 (Zanke et al 2014), but as shown they are located at different positions in the genome being far apart from TaHd044. Similarly, in a quite different part of chromosome 3A is the QTL reported by Martinez et al (2021). Nevertheless, the QTL on 3AL that might overlap with the interval of TaHd044 is detected by Luján Basile et al (2019).…”
Section: Heading Time Qtl Stable Across Environmentsmentioning
confidence: 88%
“…The latter is flanked by two previously reported SSR markers Xbarc45 (Griffiths et al 2009) and WMC264 (Zanke et al 2014), but as shown they are located at different positions in the genome being far apart from TaHd044. Similarly, in a quite different part of chromosome 3A is the QTL reported by Martinez et al (2021). Nevertheless, the QTL on 3AL that might overlap with the interval of TaHd044 is detected by Luján Basile et al (2019).…”
Section: Heading Time Qtl Stable Across Environmentsmentioning
confidence: 88%
“…An additional QTL for DTH was identified in the Avalon x Cadenza population (U.K.) on chromosome arm 3AS around the peak marker BS00021976 (169 Mb RefSeq v1.0) (Martinez et al 2021 ). This QTL interval (60 Mb at each side of BS00021976) includes 536 annotated genes, among which the authors proposed FT-A2 as a candidate of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Using our FT-A2 marker, we established that both Avalon and Cadenza carry the A10 allele, so we conclude that the D10A polymorphism is not the cause for the observed QTL for DTH on 3AS in this population. Martinez et al ( 2021 ) suggested that differences in FT-A2 transcript levels may contribute to the differences in DTH, but more precise mapping of this QTL will be necessary to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The physical positions of one of the genomic regions that we identified for heading on chromosome 5B (at 575.8 Mb) and the coincident region associated with both heading and GPC on 5A (at 586.5-588.6 Mb) coincided with the Vrn-B1 and Vrn-A1 genes, respectively. Coincident genomic regions and QTLs have been reported in several other studies (Babu et al, 2003;Lanceras et al, 2004;Quarrie et al, 2006;Pushpendra et al, 2007;Bai et al, 2013;Guan et al, 2018), which could be due to the pleiotropic effect (a single locus having effects on more than one trait simultaneously) or tight linkage (Tuberosa et al, 2002;Martinez et al, 2021).…”
Section: Crop Sciencementioning
confidence: 54%